Impacts of garlic extract on testicular oxidative stress and sperm characteristics in type 1 and 2 diabetic rats: An experimental study - Fatemeh Lotfi; Nasrin Ziamajidi; Roghayeh Abbasalipourkabir; Mohammad Taghi Goodarzi; Sara Soleimani Asl (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Hyperglycemia damages various tissues such as the testes through oxidative stress and inflammation, which can eventually lead to infertility. Objective: Garlic extract effects on the testicular tissue of diabetic rats were investigated. Materials and Methods: In this experimental study, 36 male Wistar rats (8-wk old, weighing 230-300 gr) were randomly divided into 6 groups (n = 6/each) including; C: control rats, G: received 0.4 gr of garlic extract/100 gr body weight, D1: Streptozotocin-induced-diabetic rats or type 1, D1+G: D1 rats that were treated with garlic, D2: Streptozotocin + nicotinamide-induced-diabetic rats or type 2, D2+G: D2 rats treated with garlic. At the end of the study, serum testosterone was assayed by ELISA. Also, sperm quality and quantity were evaluated. For determination of oxidative stress status, total antioxidant capacity, total oxidative status, lipid peroxidation, and thiol groups were assayed in the testis tissues of the rats by colorimetric methods. Also, inducible nitric oxide synthase (iNOS) gene expression and the protein level of interleukin-1 β (IL-1 β ) were determined by quantitative real-time polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. Results: In diabetic rats, glucose, total oxidative status and lipid peroxidation, iNOS gene expression, and IL-1 β were higher than in non-diabetic rats, whereas testosterone, total antioxidant capacity and thiol groups, and sperm quality were significantly lower compared with control rats. These alterations were normalized by garlic intervention. Conclusion: In diabetic rats, garlic was associated with reduced glucose, oxidative stress, IL-1 β , and iNOS gene expression and increased testosterone and sperm quality. So, the results suggest that garlic can reduce the severity of damage in testicular tissues of diabetic rats through its hypoglycemic, antioxidant, and anti-inflammatory properties.